Handbook of research on transnational higher education - Mukerji, Siran; Tripathi, Purnendu, 1975-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2014)
"This book is a unique compilation of the most recent research done by higher education professionals in the areas of policy, governance, technology, marketing, and leadership development, highlighting the most important strategies and policies for professionals, policy makers, administrators, and researchers interested in higher education management"--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 16, 2013).
Keywords: Transnational education; Education, Higher -- Research -- Cross-cultural studies; Universities and colleges -- Administration -- Cross-cultural studies; Education, Higher -- Marketing -- Cross-cultural studies; Educational technology -- Cross-cultural studies; Education and globalization -- Cross-cultural studies; Higher education leadership; Higher education strategies; Higher education management; Development in higher education; Quality assurance in higher education; Social media in higher education; Student support in higher education; Training in higher education; Transnational higher education; Virtual spaces and higher education; Electronic books